2016
DOI: 10.1371/journal.pone.0156871
|View full text |Cite
|
Sign up to set email alerts
|

MiR-205 and MiR-373 Are Associated with Aggressive Human Mucinous Colorectal Cancer

Abstract: Mucinous adenocarcinoma (MAC) represents a distinct histopathological entity of colorectal cancer (CRC), which is associated with disease progression and poor prognosis. Here, we found that expression levels of miR-205 and miR-373 were specifically upregulated only in patients with mucinous colon cancers, but not in CRC that lack mucinous components. To investigate the effects of miR-205 and miR-373 on intestinal epithelial cell (IEC) biology by gain- and loss-of-function experiments in a proof-of-concept appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 55 publications
2
40
0
1
Order By: Relevance
“…S2 Table shows the histopathological features of the 54 patients. Of note, our patients with CAC showed a less advanced tumor stage distribution with rarer metastasis than patients with CRC at the time of diagnosis, because all UC patients underwent increased endoscopic surveillance and tumor lesions were therefore detected at an earlier stage than in the non-UC population, as previously described [29]. This study (anonymous analysis of historical collection) abided by the Declaration of Helsinki and was approved by the local Ethics Committee of the Medical Faculty of the University Duisburg-Essen, Germany (“Ethik-Kommission der Medizinischen Fakultät der Universität Duisburg-Essen”; permit #13-5602-BO).…”
Section: Methodssupporting
confidence: 52%
“…S2 Table shows the histopathological features of the 54 patients. Of note, our patients with CAC showed a less advanced tumor stage distribution with rarer metastasis than patients with CRC at the time of diagnosis, because all UC patients underwent increased endoscopic surveillance and tumor lesions were therefore detected at an earlier stage than in the non-UC population, as previously described [29]. This study (anonymous analysis of historical collection) abided by the Declaration of Helsinki and was approved by the local Ethics Committee of the Medical Faculty of the University Duisburg-Essen, Germany (“Ethik-Kommission der Medizinischen Fakultät der Universität Duisburg-Essen”; permit #13-5602-BO).…”
Section: Methodssupporting
confidence: 52%
“…In essence, over 10% of all reported research findings of miRNA influences in cancer chemoresistance demonstrated that such a phenotype modulation was effected through simultaneous dysregulation of multiple miRNAs, rather than an individual putative chemoresistance miRNA—though no specific miRNA combination was identified as most prevalent by the authors [44,46,47,48,49,62,67,71,76,81,85,88,132,133,158,168,201,203,211,212,213,217,223,224,228,230]. This suggests that miRNA influences on cellular functions also occur at a more complex level, whereby it is a signature dysregulated expression pattern of two (or more) miRNAs that trigger simultaneous downregulation of a specific set of target transcripts leading to an ultimate change in cellular/tissue phenotype.…”
Section: Influences Of Mirnas In Cancer Chemoresistancementioning
confidence: 99%
“…In parallel, miR-373 inhibited ovarian cancer cell invasion and metastasis by targeting RAB22A (24). On the other hand, miR-373 was associated with aggressive human mucinous colorectal cancer (25). Upregulated miR-373 promoted cell migration in breast cancer through epigenetic silencing of integrin subunit α-2 (26).…”
Section: Discussionmentioning
confidence: 95%